The Editor-in-Chief's Recommendation of This Issue's Article to Readers - Burak Buldur (Cumhuriyet University, 2019)
The Editor-in-Chief's recommendation of this issue's article to readers INJURIES IN THE MAXILLOFACIAL COMPLEX AND ASSOCIATED FACTORS IN BRAZILIAN VICTIMS OF VIOLENCE: A CROSS-SECTIONAL STUDY